Method for suppressing ammonia generation in concrete and method for producing concrete with reduced ammonia generation
Patent Information
- Application Number
- JP2021010307
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-01-26
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2041-01-26
AI Technical Summary
【0016】 本発明のコンクリートのアンモニア発生抑制方法及びアンモニア発生量低減コンクリートによれば、アンモニアガスの発生量をより抑制できる。
Smart Images

Figure 0007640270000014 
Figure 0007640270000015 
Figure 0007640270000016
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for suppressing ammonia generation from concrete and a concrete having reduced ammonia generation. Manufacturing method Regarding. [Background technology]
[0002] It is generally known that art pieces such as oil paintings can become discolored due to the presence of ammonia gas in the air. In particular, in construction work for museums and other facilities, the long-term generation of ammonia gas from poured concrete, although in small amounts, is a major problem, and there is a strong demand for the establishment of technology to reduce this ammonia gas.
[0003] In the construction of art galleries and museums, a long aging period of about two years is set in order to reduce the impact of ammonia gas on artworks. This aging period is continued until the concrete is sufficiently dry and the amount of ammonia gas generated is sufficiently reduced.
[0004] However, it is clear that requiring a required period of time to mature after the construction of a museum is not efficient in terms of both construction costs and museum management. In response to these problems, for example, Patent Document 1 proposes a method for reducing ammonia gas from concrete structures, which is characterized by setting an allowable amount of ammonia gas generated from concrete and using a specific cement, a specific AE water reducing agent or high-performance water reducing agent, a specific fine aggregate, and a specific admixture to reduce the amount of ammonia gas generated from concrete to a predetermined value or less. According to the invention of Patent Document 1, it is attempted to keep the ammonia gas concentration in a building within a predetermined value and reduce it to the ammonia gas concentration level required within the construction period. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent No. 3887504 Summary of the Invention [Problem to be solved by the invention]
[0006] However, there is a demand for further reduction in the amount of ammonia gas generated from concrete.
[0007] Therefore, an object of the present invention is to provide a method for suppressing ammonia generation from concrete, which can further suppress the amount of ammonia gas generated, and concrete with reduced ammonia generation. [Means for solving the problem]
[0008] As a result of extensive investigation, the present inventors have found that a water reducing agent, which was previously thought to have no effect on the amount of ammonia gas generated, actually has a large effect on the amount of ammonia gas generated. That is, the present invention has the following aspects.
[0009] [1] A cement-containing composition containing cement, water, and a water-reducing agent. a step of confirming that the ammonia generation rate is 10 ng / (g h) or less by the following test method; The cement-containing composition Harden to form concrete and The water reducing agent is the below described The product is manufactured by the following manufacturing method. A composition comprising copolymer CP and having an ammonium ion concentration of 10 mg / L or less. R, A method for suppressing ammonia generation from concrete. <Test Method> According to the concrete mix proportions, a mixture is mixed in a beaker to a total volume of 150 mL, then the mixture is placed in a desiccator and purified air is passed through it at 1.0 L / min for 24 hours. The gas after the flow is collected in pure water and the ammonium ion concentration in the collected water is measured. The ammonium ion concentration per hour per gram of the cement-containing composition is regarded as the ammonia gas generation rate ng / (g h). <Manufacturing method of water reducing agent> A solution of poly(acrylic acid) and sulfuric acid is heated, polyethylene glycol-monomethyl ether is added, the mixture is heated under a steady flow of nitrogen, cooled to give a copolymer CP, and water is then added to the copolymer CP to give a water reducer. <Copolymer CP> Repeating unit A represented by the following formula (I) A homopolymer or copolymer comprising and, The following formula ( III ) Polyalkylene Glycol and is an esterification reaction product of , formula (I) Middle, R u Water Sohara Child can be, R v Water Sohara Child can be, M is each independently a hydrogen atom, an alkali metal ion, or an alkaline earth metal ion; Asterisks indicate binding sites; formula( III ) inside 、R 1 are independent of each other [YO] n -R 4 and Here, Y is an alkylene group having 2 to 4 carbon atoms, R 4 is a hydrogen atom, an alkyl group having 1 to 20 carbon atoms, a cyclohexyl group, or an alkylaryl group having 1 to 20 carbon atoms, n is an integer from 2 to 350. R, Copolymer.
[0010] [ka]
[0011] [ka]
[0012] [2] The method for suppressing ammonia generation from concrete according to [1], wherein the content of the water reducing agent is 0.5 to 3.0 parts by mass per 100 parts by mass of the cement. [3] The method for suppressing ammonia generation from concrete according to [1] or [2], wherein the content of the water is 10 to 80 parts by mass per 100 parts by mass of the cement. [4] The method for suppressing ammonia generation from concrete according to any one of [1] to [3], wherein the cement is one or more selected from various Portland cements and high belite cements.
[0013] [5] A cement-containing composition containing cement, water, and a water-reducing agent. a step of confirming that the ammonia generation rate is 10 ng / (g h) or less by the following test method; and hardening the cement-containing composition. The water reducing agent is The product is manufactured by the following manufacturing method. Contains copolymer CP and has an ammonium ion concentration of 10 mg / L or less Composition of in be, Concrete with reduced ammonia emissions Manufacturing method . <Test Method> According to the concrete mix proportions, a mixture is mixed in a beaker to a total volume of 150 mL, then the mixture is placed in a desiccator and purified air is passed through it at 1.0 L / min for 24 hours. The gas after the flow is collected in pure water and the ammonium ion concentration in the collected water is measured. The ammonium ion concentration per hour per gram of the cement-containing composition is regarded as the ammonia gas generation rate ng / (g h). <Water-reducing agent manufacturing method> A solution of poly(acrylic acid) and sulfuric acid is heated, polyethylene glycol-monomethyl ether is added, the mixture is heated under a steady flow of nitrogen, cooled to give a copolymer CP, and water is then added to the copolymer CP to give a water reducer. <Copolymer CP> Repeating unit A represented by the following formula (I) A homopolymer or copolymer comprising and, The following formula ( III ) Polyalkylene Glycol and is an esterification reaction product of , formula (I) Middle, R u Water Sohara Child can be, R v Water Sohara Child can be, M is each independently a hydrogen atom, an alkali metal ion, or an alkaline earth metal ion; Asterisks indicate binding sites; formula( III ) inside 、R 1 teeth, Each is independent of the other [YO] n -R 4 and Here, Y is an alkylene group having 2 to 4 carbon atoms, R 4 is a hydrogen atom, an alkyl group having 1 to 20 carbon atoms, a cyclohexyl group, or an alkylaryl group having 1 to 20 carbon atoms, n is an integer from 2 to 350. R, Copolymer.
[0014] [ka]
[0015] [ka] Effect of the Invention
[0016] According to the method for suppressing ammonia generation from concrete and the concrete for reduced ammonia generation of the present invention, the amount of ammonia gas generated can be further suppressed. [Brief description of the drawings]
[0017] [Figure 1] 1 is an example of a graph showing the ratio of ammonia generated from each material to the total amount of ammonia generated in a cement-containing composition. [Diagram 2] 1 is an example of a graph showing a comparison of the ammonia gas generation rate of each water reducing agent. [Diagram 3] 1 is an example of a graph showing the concentration of ammonium ions contained in each water reducing agent. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] <Method for suppressing ammonia generation from concrete> The method for inhibiting ammonia generation from concrete of the present invention (hereinafter also simply referred to as the "method for inhibiting ammonia generation") involves hardening a cement-containing composition containing cement, water, and a water-reducing agent to form concrete, and using a composition containing copolymer CP described below and having an ammonium ion concentration of 10 mg / L or less as the water-reducing agent. The present invention uses such a water reducing agent to reduce the amount of ammonia gas generated from concrete.
[0019] <Cement-containing composition> The cement-containing composition contains cement, water, and a water-reducing agent. In this specification, cement refers to a powder that is made primarily from limestone, clay, silica, iron oxide raw materials, etc., and hardens through a chemical reaction with water. In this specification, concrete refers to a hardened product of a cement-containing composition, which is made by mixing cement, fine aggregate (sand), and coarse aggregate (gravel (crushed stone)) and kneading with water. In this specification, fine aggregate refers to sand with a diameter of 5 mm or less. In this specification, coarse aggregate refers to gravel (crushed stone) having a diameter of more than 5 mm, and the diameter of the coarse aggregate is preferably 25 mm or less.
[0020] Examples of cement include Portland cement, blended cement, ecocement, and special cement. Examples of Portland cement include various types of Portland cement such as ordinary, early strength, extra early strength, moderate heat, low heat, and sulfate resistant.
[0021] Ordinary Portland cement is the most commonly used cement for construction and manufacturing purposes. High early strength Portland cement is a cement that provides high strength early on and continues to increase in strength over the long term. Ultra-high-early-strength Portland cement is a cement that contains more alite (C3S) and has a finer powder than high-early-strength Portland cement. Ultra-high-early-strength Portland cement develops the three-day strength of high-early-strength Portland cement in just one day. Moderate-heat Portland cement has less C3S and aluminate (C3A) and more belite (C2S) in order to reduce the heat of hydration. It has low initial strength but high long-term strength. Low-heat Portland cement has more C2S than moderate-heat Portland cement, with a C2S content of 40% or more by mass, in order to reduce the heat of hydration. Low-heat Portland cement has the characteristics of good strength development in the high-strength range and easy achievement of high fluidity in concrete with a low water-powder ratio. Sulfate-resistant Portland cement is a cement that has a low C3A content and is less reactive with sulfates. Sulfate-resistant Portland cement is suitable for construction in soil areas that contain sulfates, and also has excellent resistance to seawater.
[0022] Examples of blended cement include blast furnace cement, silica cement, and fly ash cement. Blast furnace cement is a cement mixed with blast furnace slag. Blast furnace slag is a mixture of non-iron components such as silica contained in iron ore and ash from coke combined with limestone, an auxiliary ingredient. Blast furnace slag has latent hydraulic properties and gradually hardens when stimulated by Portland cement. Blast furnace cement has low initial strength but high long-term strength. Silica cement is a cement mixed with powder of high purity silica, etc. Silica cement is used for products that are cured in an autoclave. Fly ash cement is a cement mixed with fly ash, which is produced when pulverized coal is burned. Fly ash cement has great long-term strength and can be used to create durable structures.
[0023] Ecocement is made by using more than 500 kg of waste materials, such as municipal waste incineration ash and sewage sludge, on a dry weight basis per ton of product. Ecocement is classified into normal ecocement and rapid hardening ecocement, depending on the amount of chloride ions in the cement. Ordinary ecocement is dechlorinated during the manufacturing process and has a chloride ion content of 0.1% or less. Ordinary ecocement has similar properties to ordinary Portland cement in terms of setting time and mortar compressive strength. Rapid-hardening ecocement is a type of cement with a chloride ion content of 0.5% to 1.5%. Rapid-hardening ecocement is a type of cement that has rapid hardening properties and takes advantage of its ability to develop strength at an early stage.
[0024] Special cements are manufactured as non-JIS standard products, and examples of such products include white Portland cement, alumina cement, ultra-fast hardening cement, colloidal cement, oil well cement, low heat cement, high belite cement, and cement-based solidification materials. High belite cement is a low heat cement that has been adjusted to minimize the amount of aluminate (C3A) phase, which generates a large amount of heat, among the cement components, and to have belite (C2S), which has a small heat of hydration, as the main component. High belite cement can suppress the heat of hydration, making it easy to create concrete with good fluidity. High belite cement is suitable for use in large structures.
[0025] In this embodiment, the cement is preferably any of various Portland cements and high belite cements, and among the various Portland cements, moderate heat Portland cement and low heat Portland cement are more preferable. The cement may be used alone or in combination of two or more kinds.
[0026] The cement preferably has an ammonia gas generation rate of 10 ng / (g·h) or less, more preferably 5.0 ng / (g·h) or less, and even more preferably 3.0 ng / (g·h) or less, as measured by the following test method. When the ammonia gas generation rate is equal to or less than the above upper limit, the amount of ammonia gas generated from concrete can be further suppressed. The lower limit of the ammonia gas generation rate is not particularly limited, but is, for example, 0.1 ng / (g·h) or less. <Test Method> In a beaker, add 20 mL of 0.1 N sodium hydroxide solution to 20 g of cement, stir for 30 seconds, then place in a desiccator and pass purified air through it at 1.0 L / min for 24 hours. The gas after passing through is collected in pure water and the ammonium ion concentration in the collected water is measured. The ammonium ion concentration per hour per 1 g of cement is taken as the ammonia gas generation rate ng / (g h).
[0027] In the above test method, examples of the beaker include a glass beaker, a resin beaker, a metal beaker, etc. As the beaker, a glass beaker is preferable because it is not easily corroded by strong alkali, and a Teflon (registered trademark) beaker is more preferable. The capacity of the beaker is preferably, for example, 200 to 500 mL.
[0028] In the above test method, the time for mixing the cement is not particularly limited, but is preferably 10 to 60 seconds.
[0029] In the above test method, examples of the desiccator include a glass desiccator, a resin desiccator, and a metal desiccator. As the desiccator, a glass desiccator is preferable because it is easily available and is not easily corroded. The internal volume of the desiccator is not particularly limited, but is preferably 1 to 10 L, for example.
[0030] In the above test method, examples of the purified air include air purified with activated carbon, air purified with a chemical filter, and air in a clean room. The flow rate of the air is not particularly limited, but is preferably, for example, 0.1 to 5.0 L / min. The time for which the air is passed through is not particularly limited, but is preferably, for example, 3 to 48 hours.
[0031] In the above test method, the ammonium ion concentration is determined, for example, by analysis using an ion chromatograph. The rate at which cement generates ammonia gas can be adjusted by changing the composition and type of cement.
[0032] The fine aggregate preferably has an ammonia gas generation rate of 5.0 ng / (g·h) or less, more preferably 3.0 ng / (g·h) or less, and even more preferably 1.0 ng / (g·h) or less, as measured by the following test method. When the ammonia gas generation rate is equal to or less than the above upper limit, the amount of ammonia gas generated from concrete can be further suppressed. The lower limit of the ammonia gas generation rate is not particularly limited, but is, for example, 0.1 ng / (g·h) or less. <Test Method> In a beaker, 20 g of fine aggregate is mixed with 20 mL of 0.1 N sodium hydroxide solution, stirred for 30 seconds, then placed in a desiccator and purified air is passed through it at 1.0 L / min for 24 hours. The gas after passing through is collected in pure water and the ammonium ion concentration in the collected water is measured. The ammonium ion concentration per hour per 1 g of fine aggregate is taken as the ammonia gas generation rate ng / (g h).
[0033] In the above test method, the time for stirring the fine aggregate and the sodium hydroxide aqueous solution is preferably 10 to 60 seconds. In the above test method, the type of desiccator, the internal volume of the desiccator, the air flow rate, the time for which the air is passed, and the method for determining the ammonium ion concentration are the same as those for cement. The rate at which fine aggregate generates ammonia gas can be adjusted by changing the composition and type of fine aggregate.
[0034] The coarse aggregate preferably has an ammonia gas generation rate of 10 ng / (g·h) or less, more preferably 5.0 ng / (g·h) or less, and even more preferably 3.0 ng / (g·h) or less, as measured by the following test method. When the ammonia gas generation rate is equal to or less than the above upper limit, the amount of ammonia gas generated from concrete can be further suppressed. The lower limit of the ammonia gas generation rate is not particularly limited, but is, for example, 0.1 ng / (g·h) or less. <Test Method> In a beaker, 20 g of coarse aggregate is mixed with 20 mL of 0.1 N sodium hydroxide solution, stirred for 30 seconds, then placed in a desiccator and purified air is passed through it at 1.0 L / min for 24 hours. The gas after passing through is collected in pure water and the ammonium ion concentration in the collected water is measured. The ammonium ion concentration per hour per 1 g of coarse aggregate is taken as the ammonia gas generation rate ng / (g h).
[0035] In the above test method, the time for stirring the coarse aggregate and the sodium hydroxide aqueous solution, the type of desiccator, the internal volume of the desiccator, the air flow rate, the time for which the air is passed through, and the method for determining the ammonium ion concentration are the same as those for fine aggregate. The rate at which ammonia gas is generated from coarse aggregate can be adjusted by the composition and type of coarse aggregate.
[0036] The mixing ratio of cement, fine aggregate, and coarse aggregate in concrete can be appropriately determined depending on the strength required for the concrete. The mixing ratio of cement, fine aggregate, and coarse aggregate is preferably, for example, 1 part cement, 1.5 to 4 parts fine aggregate, and 2 to 6 parts coarse aggregate by mass ratio.
[0037] A water-reducing admixture is an admixture that increases the fluidity of a cement-containing composition (fresh concrete) by electrostatic repulsion. When cement particles come into contact with water, they aggregate together and exist in the cement-containing composition. When a water-reducing admixture is added, it is adsorbed to the interface of each cement particle, dispersing the cement particles and increasing the fluidity of the cement-containing composition. Examples of water-reducing agents include normal water-reducing agents, as well as air-entraining water-reducing agents, high-performance water-reducing agents, and high-performance air-entraining water-reducing agents. AE water reducing agents are admixtures that have both cement dispersion and air entrainment properties. Air entrainment means that they uniformly entrain many independent fine air bubbles in fresh concrete, improving workability and frost resistance. High-performance water-reducing agents are defined in JIS A6204:2011 "Chemical admixtures for concrete" and are admixtures that significantly reduce the amount of water per unit volume required to obtain a desired slump, or significantly increase the slump without changing the amount of water per unit volume. High-performance water-reducing agents have higher quality performance standards than ordinary water-reducing agents. High-range air-entraining water-reducing agents are admixtures that have air-entraining properties and have higher water-reducing and better slump retention than air-entraining water-reducing agents. High-range air-entraining water-reducing agents are widely used in concrete, from ordinary strength concrete to high-strength concrete and high-fluidity concrete.
[0038] In this embodiment, the composition constituting the water-reducing agent (hereinafter also referred to as the "water-reducing agent composition") contains the following copolymer CP, and has an ammonium ion concentration of 10 mg / L or less.
[0039] <Copolymer CP> A repeating unit A represented by the following formula (I), A repeating unit B represented by the following formula (II), wherein the molar ratio of repeating unit A to repeating unit B is 10:90 to 90:10. The molar ratio A:B is 10:90 to 90:10, preferably 20:80 to 80:20, more preferably 30:70 to 80:20, and even more preferably 35:65 to 75:25. When the molar ratio A:B is within the above numerical range, the water reducing performance and the slump retention performance can be further improved.
[0040] [ka]
[0041] [ka]
[0042] In formula (I), R u are each independently a hydrogen atom or a methyl group, and preferably a hydrogen atom. R v are each independently a hydrogen atom or COOM, with COOM being preferred. Each M is independently a hydrogen atom, an alkali metal ion, or an alkaline earth metal ion, preferably an alkali metal ion or an alkaline earth metal ion, and more preferably a sodium ion, potassium ion, magnesium ion, or calcium ion. Asterisks indicate binding sites.
[0043] In formula (II), R u are each independently a hydrogen atom or a methyl group, and preferably a hydrogen atom. R v are each independently a hydrogen atom or COOM, with COOM being preferred. Each M is independently a hydrogen atom, an alkali metal ion, or an alkaline earth metal ion, preferably an alkali metal ion or an alkaline earth metal ion, and more preferably a sodium ion, potassium ion, magnesium ion, or calcium ion. m is 0, 1, 2 or 3, with 1 or 2 being preferred. p is 0 or 1, with 1 being preferred. R 1 are independent of each other [YO] n -R 4 and Y is an alkylene group having 2 to 4 carbon atoms, preferably an alkylene group having 2 to 3 carbon atoms, and more preferably an ethylene group. R 4 represents a hydrogen atom, an alkyl group having 1 to 20 carbon atoms, a cyclohexyl group, or an alkylaryl group having 1 to 20 carbon atoms, preferably an alkyl group having 1 to 20 carbon atoms, more preferably an alkyl group having 1 to 10 carbon atoms, and even more preferably an alkyl group having 1 to 4 carbon atoms. n is an integer of 2 to 350, preferably 10 to 250, more preferably 30 to 200, further preferably 35 to 150, and particularly preferably 40 to 110. Asterisks indicate binding sites.
[0044] The number average molecular weight Mn of the copolymer CP is preferably 500 to 200,000, more preferably 5,000 to 70,000, and even more preferably 15,000 to 50,000. When the number average molecular weight Mn of the copolymer CP is within the above range, the cement-containing composition can be easily processed for a long period of time. The number average molecular weight Mn of the copolymer CP is measured by gel permeation chromatography (GPC).
[0045] Copolymers CP include statistical copolymers and non-statistical copolymers. Statistical copolymers include, for example, random copolymers. Non-statistical copolymers include, for example, alternating copolymers, block copolymers, gradient copolymers, or mixtures thereof. Gradient copolymers are polymers in which the monomer composition changes continuously along the molecular chain. As the copolymer CP, a non-statistical copolymer is preferred, a block copolymer, a gradient copolymer or a mixture thereof is more preferred, and a gradient copolymer is even more preferred.
[0046] When the copolymer CP is a statistical copolymer, it is composed of at least one olefinically unsaturated carboxylic acid monomer represented by the following formula (Ia): At least one olefinically unsaturated macromonomer represented by the following formula (IIa): It can be obtained by free radical polymerization of a mixture comprising:
[0047] [ka]
[0048] [ka]
[0049] In formula (Ia), R u , R v and M is R in formula (I). u , R v , and similar to M. Bonds represented by wavy lines are meant to include both cis and trans isomers or mixtures thereof.
[0050] In formula (IIa), R u , R v , M, m, p, and R 1 R in formula (II) u , R v , M, m, p, and R 1 is the same as: Bonds represented by wavy lines are meant to include both cis and trans isomers or mixtures thereof.
[0051] Suitable conditions for carrying out free-radical polymerization are known per se to the person skilled in the art and are described, for example, in EP-A-1 103 570.
[0052] When the copolymer CP is a non-statistical copolymer, it is preferred that the copolymer CP is produced by living radical polymerization. Living radical polymerization refers to a chain polymerization system in which neither chain transfer nor termination reactions exist. In living radical polymerization, the number of active growing ends is small, and the growing ends remain active during polymerization. Examples of living radical polymerization include nitroxide-mediated polymerization (NMP), atom transfer radical polymerization (ATRP), and reversible addition-fragmentation chain transfer (RAFT) polymerization. RAFT polymerization can be achieved, for example, by using a RAFT agent (activator) and a small amount of an initiator. In RAFT polymerization, an exchange reaction in which a radical at a growing end moves to another polymer chain end occurs more rapidly than a propagation reaction by reaction with a monomer, so that all polymer chains grow uniformly. Living radical polymerization allows the preparation of block or gradient copolymers and can result in polymers with narrow molecular weight distributions, which is not possible with conventional free radical or non-living radical polymerization.
[0053] The copolymer CP can also be produced by a polymer-analogous reaction, for example, esterification of a homopolymer or copolymer containing the repeating unit A of formula (I) with a polyalkylene glycol of formula (III) below.
[0054] H.O.R. 1 (III) In formula (III), R 1 is R in formula (II) 1 is the same as:
[0055] As a method for producing the copolymer CP by esterification, the preparation method described in EP-A-1 138 697 can be mentioned, for example.
[0056] The copolymer CP may further comprise one or more monomers M in addition to the at least one olefinically unsaturated carboxylic acid monomer of formula (Ia) and the at least one olefinically unsaturated macromonomer of formula (IIa). Examples of the monomer M include styrene, ethylene, propylene, butylene, butadiene, isoprene, vinyl acetate, vinyl chloride, acrylonitrile, N-vinylpyrrolidone, hydroxyalkyl (meth)acrylate, (meth)acrylamide, maleimide, etc. Here, "(meth)acrylate" refers to either or both of acrylate and methacrylate, and "(meth)acrylamide" refers to either or both of acrylamide and methacrylamide. The monomer M may be used alone or in combination of two or more kinds.
[0057] The molar ratio of the monomer M is preferably 66 mol% or less, more preferably 50 mol% or less, even more preferably 25 mol% or less, particularly preferably 10 mol% or less, and most preferably 5 mol% or less, based on 100 mol% of all monomers forming the copolymer CP. When the molar ratio of the monomer M is equal to or less than the upper limit, the water reducing performance and slump retention performance can be further improved. The molar ratio of the monomer M may be 0 mol% based on 100 mol% of all monomers forming the copolymer CP.
[0058] The molar ratio of the repeating unit A and the repeating unit B in the copolymer CP is preferably 34 mol% or more, more preferably 50 mol% or more, even more preferably 75 mol% or more, particularly preferably 90 mol% or more, and most preferably 95 mol% or more, based on 100 mol% of all monomers forming the copolymer CP. When the molar ratio of the repeating unit A and the repeating unit B is equal to or more than the lower limit, the water reducing performance and the slump retention performance can be further improved. The molar ratio of the repeating unit A and the repeating unit B may be 100 mol% based on 100 mol% of all monomers forming the copolymer CP.
[0059] The content of the copolymer CP in the water reducing agent composition is, for example, preferably 1 to 99 mass%, more preferably 10 to 90 mass%, and even more preferably 20 to 80 mass%, based on the total mass of the water reducing agent composition. When the content of the copolymer CP is equal to or more than the lower limit, the water reducing performance and the slump retention performance can be further improved. When the content of the copolymer CP is equal to or less than the upper limit, the viscosity of the water reducing agent composition can be reduced, making it easy to handle.
[0060] The water-reducing agent composition may contain other components in addition to the copolymer CP, such as water, plasticizers, AE admixtures, defoamers, antifoamers, retarders, solidification accelerators, hardening accelerators, hydrophobizing agents, and humus inhibitors. The content of the other components is not particularly limited, but is preferably, for example, 10 to 50 mass % relative to the total mass of the water-reducing agent composition.
[0061] The water-reducing agent composition preferably has an ammonia gas generation rate of 10 ng / (g·h) or less, more preferably 5.0 ng / (g·h) or less, and even more preferably 3.0 ng / (g·h) or less, as measured by the following test method. When the ammonia gas generation rate is equal to or less than the above upper limit, the amount of ammonia gas generated from concrete can be further suppressed. The lower limit of the ammonia gas generation rate is not particularly limited, but is, for example, 0.1 ng / (g·h) or less. <Test Method> In a beaker, 20 g of the water-reducing agent composition is mixed with 20 mL of 0.1 N sodium hydroxide solution, stirred for 30 seconds, then placed in a desiccator and purified air is passed through it at 1.0 L / min for 24 hours. The gas after passing through is collected in pure water and the ammonium ion concentration in the collected water is measured, and the ammonium ion concentration per hour per gram of the water-reducing agent composition is taken as the ammonia gas generation rate ng / (g h).
[0062] In the above test method, the time for stirring the water-reducing agent composition and the sodium hydroxide aqueous solution, the type of desiccator, the internal volume of the desiccator, the air flow rate, the time for which the air is passed through, and the method for determining the ammonium ion concentration are the same as those for fine aggregate. The rate at which the water-reducing agent composition generates ammonia gas can be adjusted by adjusting the composition and type of the water-reducing agent composition.
[0063] The ammonium ion concentration of the water-reducing agent composition is 10 mg / L or less, preferably 5.0 mg / L or less, and more preferably 1.0 mg / L or less. When the ammonium ion concentration of the water-reducing agent composition is the above upper limit or less, the amount of ammonia gas generated can be further suppressed. The lower limit of the ammonium ion concentration in the water-reducing agent composition is not particularly limited, but is, for example, 0.1 mg / L. The ammonium ion concentration of the water-reducing agent composition can be determined by analysis using an ion chromatograph.
[0064] The content of the water reducing agent relative to 100 parts by mass of cement is preferably 0.5 to 3.0 parts by mass, more preferably 0.6 to 2.5 parts by mass, and even more preferably 0.8 to 2.0 parts by mass. When the content of the water reducing agent is equal to or more than the lower limit, the fluidity of the cement-containing composition can be further increased. When the content of the water reducing agent is equal to or less than the upper limit, the amount of ammonia gas generated can be further suppressed.
[0065] The content of water relative to 100 parts by mass of cement is preferably 10 to 80 parts by mass, more preferably 25 to 60 parts by mass, and even more preferably 30 to 50 parts by mass. When the content of water is equal to or more than the lower limit, the fluidity of the cement-containing composition can be further increased. When the content of water is equal to or less than the upper limit, heat generation during mixing can be suppressed. Here, the water content does not include water contained in the water-reducing agent composition.
[0066] The cement-containing composition may contain components other than cement, water, and a water-reducing agent (hereinafter also referred to as "optional components"). Examples of optional components include fine aggregate, coarse aggregate, and admixtures other than water reducing agents. Examples of the admixture other than the water-reducing agent include a hardening accelerator, a setting retarder, a waterproofing agent, a foaming agent, a thickener, etc. However, the admixture other than the water-reducing agent does not include other components contained in the water-reducing agent composition. The content of the optional components relative to the total mass of the cement-containing composition is not particularly limited, but is preferably, for example, 10 to 20 mass %.
[0067] Ammonia is thought to move through the concrete in the form of an aqueous solution and be generated from the surface of the concrete. The mechanism by which ammonia is generated is thought to be as follows. In the pores of concrete, there exists a high pH aqueous solution (pore solution) based on the cement hydration reaction equations ((1)-(3)). CaO+H2O ⇒ Ca 2+ +2OH - (1) Na2O+H2O ⇒ 2Na + +2OH - (2) K2O+H2O ⇒ 2K + +2OH - (3) This pore solution hydrolyzes nitrogen-containing compounds on the aggregate surface and in the cement, generating water-soluble amine compounds and ammonium ions.
[0068] Ammonium ion and ammonia are in equilibrium in water as follows ((4)~(5)). NH3+H2O ⇔ NH4 + +OH - (4) K = [NH4 + ]×[OH - ] / [NH3] ···(5) In formula (5), [NH4 + ] is the concentration of ammonium ions, [OH - ] represents the concentration of hydroxide ions, and [NH3] represents the concentration of ammonia. The equilibrium constant, K, is 1.77 x 10 at 25°C. -5 The [OH - ] is about 0.1M even 80 days after casting, and NH3 is NH4 + This makes it easy for gaseous ammonia to be produced.
[0069] The method for suppressing ammonia generation of this embodiment uses a water-reducing agent containing copolymer CP as a water-reducing agent composition. Copolymer CP has a specific structural unit, and does not use a compound containing ammonium ions as an initiator. Therefore, the method for suppressing ammonia generation of this embodiment can further suppress the amount of ammonia gas generated from concrete.
[0070] <Concrete with reduced ammonia emissions> The concrete for reducing ammonia emission of the present invention is produced by hardening a cement-containing composition that contains cement, water, aggregates (fine aggregate, coarse aggregate), and a water-reducing agent. The water reducing agent contains the above-mentioned copolymer CP and has an ammonium ion concentration of 10 mg / L or less. The concrete with reduced ammonia generation of the present invention has an ammonia gas generation rate of 10 ng / (g·h) or less, preferably 5.0 ng / (g·h) or less, and more preferably 1.0 ng / (g·h) or less, of the cement-containing composition measured by the following test method. When the ammonia gas generation rate is equal to or less than the above upper limit, the amount of ammonia gas generated from the concrete with reduced ammonia generation can be further suppressed. The lower limit of the ammonia gas generation rate is not particularly limited, but is, for example, 0.1 ng / (g·h) or less. <Test Method> According to the concrete mix ratio, mix in a beaker to a total volume of 150 mL, place in a desiccator, and pass purified air through it at 1.0 L / min for 24 hours. The gas after passing through is collected in pure water, and the ammonium ion concentration in the collected water is measured. The ammonium ion concentration per hour per gram of the cement-containing composition is taken as the ammonia gas generation rate ng / (g h).
[0071] In the above test method, the time for mixing the cement-containing composition is preferably 10 to 60 seconds. In the above test method, the type of desiccator, the internal volume of the desiccator, the air flow rate, the time for passing air, and the method for determining the ammonium ion concentration are the same as those for cement. The rate at which the cement-containing composition generates ammonia gas can be adjusted by the composition and type of the cement-containing composition.
[0072] The composition of the water-reducing agent is the same as that of the water-reducing agent composition described above.
[0073] The concrete for reduced ammonia generation of this embodiment uses the above-mentioned water-reducing agent composition, and therefore can further reduce the amount of ammonia gas generated from concrete. EXAMPLES
[0074] The present invention will be described in more detail below using examples, but the present invention is not limited to these examples.
[0075] Taking advantage of the fact that ammonia gas is generated by adding an alkaline aqueous solution to the constituent materials of concrete, we compared the amount of ammonia generated by concrete and examined mix designs.
[0076] Commonly used cement C, fine aggregate S, coarse aggregate G, and admixture (water-reducing agent) Ad were obtained and used from five operating ready-mix concrete plants (A, B, C, D, E).
[0077] <Ammonia gas generation from concrete materials (cement-containing compositions)> 20 g of each material was weighed out into a Teflon (registered trademark) beaker, 20 mL of 0.1 N aqueous sodium hydroxide solution was added, and the mixture was stirred for 30 seconds. The beaker was placed in a 6 L glass desiccator, and clean room air that had been further purified with an activated carbon chemical filter was passed through it at a rate of 1.0 L / min. The air was then passed through an impinger, and the generated ammonia gas was collected in pure water. The ammonium ion concentration in the collected water was analyzed using an ion chromatograph, and the ammonia generation rate (ng / (g·h)) was calculated.
[0078] <Ammonia gas generation from concrete specimens> The materials were weighed out and mixed in a Teflon (registered trademark) beaker according to the composition of each plant, with a total volume of 150 mL. The beaker was placed in the desiccator and the amount of ammonia generated with hardening was measured over time, and the generation rate (mg / (m 3 ·h) was calculated.
[0079] <Evaluation of water-reducing agent properties> Five types of high-performance AE water-reducing agents (I, II, III, IV, and V) obtained from the manufacturer were used as admixtures. The ammonium ion concentration (mg / L) in each water-reducing agent was measured using ion chromatography.
[0080] [Experimental Examples 1-5] For each material listed in Table 1, the ammonia generation rate generated from each material after kneading with the aqueous sodium hydroxide solution was measured over time. The results are shown in Table 1. In Table 1, "0-3 hr" indicates that the generation rate was calculated from the amount of ammonia collected between 0 and 3 hours after the aqueous sodium hydroxide solution was added and kneading was started. "3-18 hr" indicates that the generation rate was calculated from the amount of ammonia collected between 3 and 18 hours after the aqueous sodium hydroxide solution was added and kneading was started. "18-22 hr" indicates that the generation rate was calculated from the amount of ammonia collected between 18 and 22 hours after the aqueous sodium hydroxide solution was added and kneading was started.
[0081] [Table 1]
[0082] As shown in Table 1, differences in the rate at which ammonia gas is generated were observed between materials at each plant, with the difference in generation rate being particularly noticeable immediately after mixing (0-3 hours). The difference in generation rate was in the range of several times between cements, but between fine and coarse aggregates, differences of around 10 times were observed. In particular, with water-reducing agents, the amount of ammonia gas generated could reach tens of thousands of times that of other materials, and differences in generation rate between water-reducing agents could be more than 10 times. It was found that large amounts of ammonia gas were generated from the water-reducing agent. Although the amount of water-reducing agent added was small, at 0.1 to 0.2% by mass of the total concrete and 0.5 to 3.0% by mass of the cement, the amount of ammonia gas generated could be several thousand times that of the cement.
[0083] An example of the ratio of ammonia generated from the water-reducing agent to the total amount of ammonia generated (Experimental Example 3) is shown in Figure 1. As shown in Figure 1, the ratio was particularly high for the first 3 hours after mixing, with ammonia generated from the water-reducing agent accounting for more than 90%.
[0084] [Experimental Example 6] In order to confirm the difference in the rate of ammonia gas generation due to differences in the type of water-reducing agent, the amount of ammonia gas generated by adding an aqueous sodium hydroxide solution was measured using five types of high-performance AE water-reducing agents (I, II, III, IV, and V). Water-reducing agent IV is a water-reducing agent to which the present invention is applied, while water-reducing agents I to III and V are water-reducing agents outside the scope of application of the present invention. The water reducing agent IV is an aqueous solution containing 40 mass % of copolymer CP (number average molecular weight 11,500, acid value 69 mgKOH / g) obtained by the following method. A glass reactor equipped with a thermometer, stirrer, gas inlet tube, and distillation assembly was charged with 160 g of an aqueous solution of partially neutralized poly(acrylic acid) having a molecular weight of 4000 and 7.5 g of 50% by weight sulfuric acid. The solution was heated to 70° C., and 400 g of polyethylene glycol-monomethyl ether having a number average molecular weight of 1000 was added. The mixture was heated under a steady flow of nitrogen and stirred at 165°C for 4 hours, after which a sample was taken and cooled to 90°C, followed by the addition of water to obtain Water Reducer IV.
[0085] FIG. 2 shows a comparison of the ammonia gas generation rate of each water-reducing agent. As shown in FIG. 2, a large amount of ammonia gas was generated from water-reducing agent I. On the other hand, water-reducing agent IV to which the present invention is applied generated very little ammonia gas, and at 0 to 3 hours, a difference of more than 10,000 times was observed compared to water-reducing agent I. Although the generation of ammonia gas attenuated early after 3 hours for all water-reducing agents, the total amount generated was expected to be large, and it was confirmed that it is important to select a water-reducing agent that generates less ammonia gas in order to further suppress the amount of ammonia gas generated.
[0086] [Experimental Example 7] Figure 3 shows the results of measuring the ammonium ion concentration contained in each water-reducing agent. As shown in Figure 3, water-reducing agents I and III had high ammonium ion concentrations, which supports the results of Experimental Example 6. Although water-reducing agent V had a low ammonium ion concentration, it generated a lot of ammonia gas in Experimental Example 6, confirming that it is difficult to judge differences in the amount of ammonia gas generated simply from the ammonium ion concentration alone. Therefore, it was confirmed that in order to further reduce the amount of ammonia gas generated, it is important to adjust the composition, molecular weight, and type of catalyst (initiator) of the polymer contained in the water reducer.
Claims
1. A step of confirming that the ammonia generation rate of a cement-containing composition containing cement, water, and a water-reducing agent is 10 ng / (g h) or less by the following test method; and hardening the cement-containing composition to form concrete. The water reducing agent is a composition produced by the production method described below, contains the copolymer CP described below, and has an ammonium ion concentration of 10 mg / L or less. <Test Method> According to the concrete mix proportions, a mixture is mixed in a beaker to a total volume of 150 mL, and then the mixture is placed in a desiccator and purified air is passed through it at 1.0 L / min for 24 hours. The gas after the passage is collected in pure water and the ammonium ion concentration in the collected water is measured. The ammonium ion concentration per hour per gram of the cement-containing composition is defined as the ammonia gas generation rate ng / (g·h). <Method of manufacturing water-reducing agent> A solution of poly(acrylic acid) and sulfuric acid is heated, polyethylene glycol-monomethyl ether is added, the mixture is heated under a steady flow of nitrogen, and cooled to obtain a copolymer CP, and then water is added to the copolymer CP to obtain a water reducer. <Copolymer CP> A homopolymer or copolymer containing a repeating unit A represented by the following formula (I), 【Chemistry 1】 It is an esterification reaction product with a polyalkylene glycol represented by the following formula (III): 【Chemistry 2】 In formula (I), R u is a hydrogen atom, Rv is a hydrogen atom; M is each independently a hydrogen atom, an alkali metal ion, or an alkaline earth metal ion; Asterisks indicate binding sites; In formula (III), R 1 is each independently [YO] n -R 4 and where Y is an alkylene group having 2 to 4 carbon atoms, R 4 represents a hydrogen atom, an alkyl group having 1 to 20 carbon atoms, a cyclohexyl group, or an alkylaryl group having 1 to 20 carbon atoms, A copolymer, wherein n is an integer from 2 to 350.
2. The method for suppressing ammonia generation from concrete according to claim 1, wherein the content of the water reducing agent is 0.5 to 3.0 parts by mass relative to 100 parts by mass of the cement.
3. The method for suppressing ammonia generation from concrete according to claim 1 or 2, wherein the content of the water is 10 to 80 parts by mass relative to 100 parts by mass of the cement.
4. The method for suppressing ammonia generation from concrete according to any one of claims 1 to 3, wherein the cement is one or more selected from various Portland cements and high belite cements.
5. A step of confirming that the ammonia generation rate of a cement-containing composition containing cement, water, and a water-reducing agent is 10 ng / (g h) or less by the following test method; and hardening the cement-containing composition. The water reducing agent is produced by the following production method, contains the following copolymer CP, and is a composition having an ammonium ion concentration of 10 mg / L or less. <Test Method> According to the concrete mix proportions, a mixture is mixed in a beaker to a total volume of 150 mL, and then the mixture is placed in a desiccator and purified air is passed through it at 1.0 L / min for 24 hours. The gas after the passage is collected in pure water and the ammonium ion concentration in the collected water is measured. The ammonium ion concentration per hour per gram of the cement-containing composition is defined as the ammonia gas generation rate ng / (g·h). <Method of manufacturing water-reducing agent> A solution of poly(acrylic acid) and sulfuric acid is heated, polyethylene glycol-monomethyl ether is added, the mixture is heated under a steady flow of nitrogen, and cooled to obtain a copolymer CP, and then water is added to the copolymer CP to obtain a water reducer. <Copolymer CP> A homopolymer or copolymer containing a repeating unit A represented by the following formula (I), 【Chemistry 3】 It is an esterification reaction product with a polyalkylene glycol represented by the following formula (III): 【Chemistry 4】 In formula (I), R u is a hydrogen atom, R v is a hydrogen atom, M is each independently a hydrogen atom, an alkali metal ion, or an alkaline earth metal ion; Asterisks indicate binding sites; In formula (III), R 1 is each independently [YO] n -R 4 and where Y is an alkylene group having 2 to 4 carbon atoms, R 4 represents a hydrogen atom, an alkyl group having 1 to 20 carbon atoms, a cyclohexyl group, or an alkylaryl group having 1 to 20 carbon atoms, A copolymer, wherein n is an integer from 2 to 350.
Citation Information
Patent Citations
Method for reducing ammonia gas generated from concrete structure and method for predicting amount of ammonia gas generated from concrete
JP2000248643A
Cement generating small amount of gaseous ammonia, estimation method for the same and concrete generating small amount of gaseous ammonia
JP2001002454A
Polymer for cement-dispersing admixture
JP2002003526A
Use of polymer dispersion, polymeric powder and polymeric granule free from ammonia as admixture for inorganic construction material construction material using the above and method of improving mechanical strength
JP2002137948A
Low outgassing mortar or concrete
JP2006036555A